2005
DOI: 10.1097/01.ju.0000158121.49085.ba
|View full text |Cite
|
Sign up to set email alerts
|

Cd70: A New Tumor Specific Biomarker for Renal Cell Carcinoma

Abstract: Our study identified CD70 as a new specific tumor marker for clear cell RCC. This new marker can be used for differential diagnosis in cases of uncertain histological classification. The function of this protein in tumorigenesis and its use as a diagnostic marker in serum and urine or as a therapeutic tool must be investigated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 16 publications
2
43
2
Order By: Relevance
“…Our studies showed a high-level expression of CD70 on RCC cells that might be expected to induce a strong immune response against the tumour. Frequent expression of CD70 on RCC was recently also reported by Junker et al (2005). Although RCC is known to be a highly immunogenic tumour, it is also a very aggressive cancer that is clearly able to escape immune surveillance.…”
Section: Discussionmentioning
confidence: 62%
“…Our studies showed a high-level expression of CD70 on RCC cells that might be expected to induce a strong immune response against the tumour. Frequent expression of CD70 on RCC was recently also reported by Junker et al (2005). Although RCC is known to be a highly immunogenic tumour, it is also a very aggressive cancer that is clearly able to escape immune surveillance.…”
Section: Discussionmentioning
confidence: 62%
“…CD5 can focally be expressed in type B3 thymoma, urothelial carcinoma, malignant mesothelioma, and adenocarcinoma of various organs; 33 CD70 may be positive in renal cell carcinoma, nasopharyngeal carcinoma, and Hodgkin lymphoma. 34 Clear cell carcinoma of the thymus is exceedingly rare; [35][36][37][38] we have only seen two cases in our database of B120 thymic carcinomas. In addition to renal clear cell carcinomas, metastatic germ cell tumors (particularly seminoma), large B cell lymphoma, clear cell sarcoma or melanoma, and clear cell paraganglioma should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Altered CD70 expression was found in hematologic malignancies and also in solid tumors, such as nasopharyngeal carcinoma, thymic carcinoma, and brain tumors (9). The most frequent expression was reported in RCC (10)(11)(12)(13), but the mechanism that leads to the upregulation of CD70 in this tumor type is still unclear. Interestingly, CD70 expression is less prevalent in VHL unrelated RCC subtypes.…”
Section: Introductionmentioning
confidence: 99%